Diversity of the genus Polylepis (Rosaceae, Sanguisorbeae) in the Peruvian Andes - Mendoza, Wilfredo (2011)
This study provides information on the diversity of Peruvian species of Polylepis. Nineteen (19) species are reported here (more than 70% of the 27 species registered for the whole Andean region). As a result, Peru could be considered as the country with the largest diversity of Polylepis species, in comparison with Bolivia (13), Ecuador (7), Argentina (4), Colombia (3), Chile (2), and Venezuela (1). The species occur in 19 departments of Peru, with the majority of them in Cusco (10) and Ayacucho (8). Species diversity is mostly concentrated in the Peruvian southern Andes (15 species), with the region becoming the potential center of diversification of the genus Polylepis. Regarding their altitudinal distribution, the greatest diversity (18) is found between 3000 and 4000 m.